2023
DOI: 10.3389/fphys.2022.999011
|View full text |Cite
|
Sign up to set email alerts
|

Danger signals in traumatic hemorrhagic shock and new lines for clinical applications

Abstract: Hemorrhage is the leading cause of death in severe trauma injuries. When organs or tissues are subjected to prolonged hypoxia, danger signals—known as damage-associated molecular patterns (DAMPs)—are released into the intercellular environment. The endothelium is both the target and a major provider of damage-associated molecular patterns, which are directly involved in immuno-inflammatory dysregulation and the associated tissue suffering. Although damage-associated molecular patterns release begins very early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…By assessing the patient's disease severity and employing a targeted approach to fluid infusion, restrictive fluid resuscitation ensures the rationality of the infusion process, ultimately improving blood volume, enhancing cardiac function, and contributing to favorable prognoses [9]. Its primary benefits are summarized as follows [7][8][9][10] Through comparative analysis, this study revealed a lower incidence of complications in the study group, suggesting that the restrictive fluid resuscitation protocol is associated with reduced complications and enhanced safety, minimizing the disruption of the internal environment, which may be closely related to the regimen's restrictions on infusion volume and speed, thereby helping maintain a dynamic equilibrium between the body's coagulation and fibrinolytic systems and ultimately reducing blood loss [13,14].…”
Section: Discussionmentioning
confidence: 84%
“…By assessing the patient's disease severity and employing a targeted approach to fluid infusion, restrictive fluid resuscitation ensures the rationality of the infusion process, ultimately improving blood volume, enhancing cardiac function, and contributing to favorable prognoses [9]. Its primary benefits are summarized as follows [7][8][9][10] Through comparative analysis, this study revealed a lower incidence of complications in the study group, suggesting that the restrictive fluid resuscitation protocol is associated with reduced complications and enhanced safety, minimizing the disruption of the internal environment, which may be closely related to the regimen's restrictions on infusion volume and speed, thereby helping maintain a dynamic equilibrium between the body's coagulation and fibrinolytic systems and ultimately reducing blood loss [13,14].…”
Section: Discussionmentioning
confidence: 84%
“…When compounded by tissue injury, this so-called haemorrhagic shock is capable of triggering TIC. Injurious insults to tissues lead to extensive necrosis, provoking the release of damage-associated molecular patterns (DAMPs), such as histones, HMGB1, polyphosphates (e.g., ATP), and nuclear and mitochondrial DNA, which are capable of engaging cells of the innate immune system by signalling via pattern recognition receptors [ 21 , 22 , 23 , 24 , 25 ]. Physical trauma also triggers an inflammatory response, characterised by a cytokine “breeze” or “storm”, depending on the severity of the injury [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, 60,000 people die in the United States as a result of traumatic hemorrhage, and 1.5 million people die worldwide as a result of physical trauma [5] [6]. Approximately 60% and 25% of all trauma-related deaths are attributed to immediate and early mortality, respectively, while the remaining 10% to 30% of deaths are attributed to late mortality [7]. According to data from the World Health Organization (WHO), injuries account for over 5 million fatalities globally year, and by 2030, injury mortality is predicted to rise sharply.…”
Section: Introductionmentioning
confidence: 99%